Early amplitude-integrated electroencephalography for monitoring neonates at high risk for brain injury - Gabriel Fernando Todeschi Variane; Maurício Magalhães; Renato Gasperine; Heitor Castelo Branco Rodrigues Alves; Thiago Luiz Pereira Donoso Scoppetta; Rodrigo de Jesus Gonçalves Figueredo; Francisco Paulo Martins Rodrigues; Alexandre Netto; Marcelo Jenne Mimica; Clery Bernardi Gallacci (Elsevier, 2017)
Objective: This study aimed to correlate amplitude-integrated electroencephalography findings with early outcomes, measured by mortality and neuroimaging findings, in a prospective cohort of infants at high risk for brain injury in this center in Brazil. Methods: This blinded prospective cohort study evaluated 23 preterm infants below 31 weeks of gestational age and 17 infants diagnosed with hypoxic-ischemic encephalopathy secondary to perinatal asphyxia, with gestational age greater than 36 weeks, monitored with amplitude-integrated electroencephalography in a public tertiary center from February 2014 to January 2015. Background activity (classified as continuous, discontinuous high-voltage, discontinuous low-voltage, burst-suppression, continuous low-voltage, or flat trace), presence of sleep-wake cycling, and presence of seizures were evaluated. Cranial ultrasonography in preterm infants and cranial magnetic resonance imaging in infants with hypoxic-ischemic encephalopathy were performed. Results: In the preterm group, pathological trace or discontinuous low-voltage pattern (p = 0.03) and absence of sleep-wake cycling (p = 0.019) were associated with mortality and brain injury assessed by cranial ultrasonography. In patients with hypoxic-ischemic encephalopathy, seizure patterns on amplitude-integrated electroencephalography traces were associated with mortality or brain lesion in cranial magnetic resonance imaging (p = 0.005). Conclusion: This study supports previous results and demonstrates the utility of amplitude-integrated electroencephalography for monitoring brain function and predicting early outcome in the studied groups of infants at high risk for brain injury. Resumo: Objetivo: Este estudo visou correlacionar os achados do eletroencefalograma de amplitude integrada (aEEG) com resultados precoces, medidos por mortalidade e achados de neuroim- agem, em uma coorte prospectiva de neonatos com risco elevado de lesão cerebral em nosso centro no Brasil. Métodos: O estudo prospectivo de coorte cego avaliou 23 neonatos prematuros abaixo de 31 semanas de idade gestacional (IG) e 17 neonatos diagnosticados com Encefalopatia Hipóxico-Isquêmica (EHI) secundária à asfixia perinatal, com IG superior a 36 semanas, monitorados com aEEG em um centro terciário público de fevereiro de 2014 a janeiro de 2015. Foram avaliadas a atividade de base (classificada como padrão contínuo, descontínuo de alta voltagem, descontínuo de baixa voltagem, supressão de explosão, contínuo de baixa voltagem ou traço plano), a presença de ciclo do sono-vigília e a presença de convulsões. Foram feitas a ultrassonografia craniana em prematuros e a ressonância magnética (RM) craniana em neonatos com EHI. Resultados: No grupo de prematuros, o traço patológico ou padrão descontínuo de baixa voltagem (p = 0,03) e a ausência de ciclo do sono-vigília (p = 0,019) foram associados a mortalidade e lesão cerebral avaliada por ultrassonografia craniana. Em pacientes com EHI, os padrões de convulsão nos traçados do aEEG foram associados a mortalidade ou lesão cerebral na RM craniana (p = 0,005). Conclusão: Este estudo corrobora os resultados anteriores e demonstra a utilidade do aEEG no monitoramento da função cerebral e na predição de alterações precoces nos grupos de neonatos estudados com risco elevado de lesão cerebral. Keywords: Newborn, Brain injury, Amplitude-integrated EEG, Early outcome, Palavras-chave: Recém-nascido, Lesão cerebral, EEG de amplitude integrada, Resultado precoce